2021
DOI: 10.3390/genes12101543
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and Genomic Pathways of Melanoma Development, Invasion and Metastasis

Abstract: Melanoma is a serious form of skin cancer that accounts for 80% of skin cancer deaths. Recent studies have suggested that melanoma invasiveness is attributed to phenotype switching, which is a reversible type of cell behaviour with similarities to epithelial to mesenchymal transition. Phenotype switching in melanoma is reported to be independent of genetic alterations, whereas changes in gene transcription, and epigenetic alterations have been associated with invasiveness in melanoma cell lines. Here, we revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 161 publications
(206 reference statements)
0
11
0
Order By: Relevance
“…The biological functions of VEGF-A are exerted through its binding to two tyrosine kinase receptors, VEGFR1 and VEGFR2, expressed in vascular endothelial cells. VEGF-A plays an important role in tumor angiogenesis by enhancing the proliferation and motility of endothelial cells (Motwani and Eccles 2021). Several studies have shown that various cancer cells produce VEGF-A and express its receptors, VEGFR1 and/or VEGFR2 (von Marschall et al 2000;Carrillo de Santa Pau et al 2009;Hlobilkova et al 2009;Sopo et al 2019).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The biological functions of VEGF-A are exerted through its binding to two tyrosine kinase receptors, VEGFR1 and VEGFR2, expressed in vascular endothelial cells. VEGF-A plays an important role in tumor angiogenesis by enhancing the proliferation and motility of endothelial cells (Motwani and Eccles 2021). Several studies have shown that various cancer cells produce VEGF-A and express its receptors, VEGFR1 and/or VEGFR2 (von Marschall et al 2000;Carrillo de Santa Pau et al 2009;Hlobilkova et al 2009;Sopo et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“… 1998 ; Guo et al . 2021 ; Motwani and Eccles 2021 ). VEGF is a potent angiogenic factor that binds to two tyrosine kinase-type receptors, VEGF receptor-1 (VEGFR1)/fms-like tyrosine kinase (Flt-1) and VEGFR2/kinase insert domain receptor (KDR)/fetal liver kinase 1, which are specifically and highly expressed in vascular endothelial cells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanism involved in tumor development and dissemination of cancer cells is still poorly understood and numerous proteins, miRNAs and signaling pathways have been reported to regulate this process [1,2]. Among these, endoglin, an auxiliary receptor of the transforming growth factor b (TGF-b) family, has emerged as a promising therapeutic target [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Increasing evidences showed that many genes involved the development and progression of melanoma, most recurrent mutation is BRAFV600E, which hyperactivates the mitogen-activated protein kinase (MAPK) pathway ( 3 ) followed by NRAS mutation ( 4 ) and NF1 mutations ( 5 ). Among the regulatory pathways implicated in melanoma, MAPK pathway is most common, others include PI3K pathway, Wingless type MMTV integration site (Wnt) signaling ( 6 ). Although the treatment of melanoma has been greatly improved in recent years, the prognosis of tumor patients remains poor due to individual differences.…”
Section: Introductionmentioning
confidence: 99%